Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.rmcr.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

The sodium-phosphate co-transporter SLC34A2, and pulmonary alveolar microlithiasis: Presentation of an inbred family and a novel truncating mutation in exon 3

Abstract: Pulmonary alveolar microlithiasis is a disorder in which many tiny fragments (microliths) of calcium phosphate gradually accumulate in alveoli. Loss of function mutations in the gene SLC34A2 coding for the sodium phosphate co-transporter (NaPi-IIb) are responsible for genetic forms of alveolar microlithiasis.We now report a consanguineous Italian family from Calabria with two affected members segregating alveolar microlithiasis in a recessive fashion. We describe, for the first time, a novel loss of function m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 18 publications
0
11
0
3
Order By: Relevance
“…In Corut et al 2 first reported that SLC34A2 mutations cause PAM, and subsequent studies have also described mutations in this gene in patients with PAM. 3 , 4 Here, we report a case of PAM with a compound heterozygous mutation in SLC34A2 that includes a novel mutation in exon 12.…”
mentioning
confidence: 94%
“…In Corut et al 2 first reported that SLC34A2 mutations cause PAM, and subsequent studies have also described mutations in this gene in patients with PAM. 3 , 4 Here, we report a case of PAM with a compound heterozygous mutation in SLC34A2 that includes a novel mutation in exon 12.…”
mentioning
confidence: 94%
“…La primera descripción histopatológica de la microlitiasis alveolar pulmonar la realizó Harbitz en 1918, pero la denominación y descripción de la misma no fue realizada sino hasta 1933 por Puhr 3 . Posteriormente se hicieron más reportes de esta patología y hasta el momento se cuenta con alrededor de 700 casos descritos en la literatura internacional 4,5 . La mayoría de estos casos se reportan principalmente en Europa y Asia, particularmente en Italia y Turquía 3,4 .…”
Section: Discussionunclassified
“…La falla en la recaptación de ion fosfato, necesario para la síntesis de fosfolípidos del surfactante a nivel intracelular, resulta en la precipitación de fosfato de calcio y la formación de microlitos en el espacio alveolar 9 . Los microlitos aumentan en volumen y al entrar en contacto con las paredes alveolares desencadenan un proceso fibrótico 5,8 . La composición de los microlitos consta principalmente de fosfato de calcio, hidroxiapatita o carboxiapatita 10 ; además, contiene depósitos de hierro, zinc, aluminio, sílice y magnesio 3 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…In a few patients, heterozygous mutations were linked to testicular microlithiasis but this has not been replicated by independent studies [15]. At present, 20 distinct mutations have been reported, including deletions, frame shifts, missense mutations as well as changes in potential splice sites and in the promoter region [15,98,37,40,89,42,102,106,20,66,75,39].…”
Section: Human Disease Associated With Napi-iib (Slc34a2) Mutationsmentioning
confidence: 99%